De novo variants cause complex symptoms in HSP-ATL1 (SPG3A) and uncover genotype–phenotype correlations. Issue 1 (4th August 2022) - Alecu, Julian E; Saffari, Afshin; Jordan, Catherine; Srivastava, Siddharth; Blackstone, Craig; Ebrahimi-Fakhari, Darius
Abstract: Pathogenic variants in ATL1 are a known cause of autosomal-dominantly inherited hereditary spastic paraplegia (HSP- ATL1, SPG3A) with a predominantly 'pure' HSP phenotype. Although a relatively large number of patients have been reported, no genotype–phenotype correlations have been established for specific ATL1 variants. Confronted with five children carrying de novo ATL1 variants showing early, complex and severe symptoms, we systematically investigated the molecular and phenotypic spectrum of HSP- ATL1 . Through a cross-sectional analysis of 537 published and novel cases, we delineate a distinct phenotype observed in patients with de novo variants. Guided by this systematic phenotyping approach and structural modelling of disease-associated variants in atlastin-1, we demonstrate that this distinct phenotypic signature is also prevalent in a subgroup of patients with inherited ATL1 variants and is largely explained by variant localization within a three-dimensional mutational cluster. Establishing genotype–phenotype correlations, we find that symptoms that extend well beyond the typical pure HSP phenotype (i.e. neurodevelopmental abnormalities, upper limb spasticity, bulbar symptoms, peripheral neuropathy and brain imaging abnormalities) are prevalent in patients with variants located within this mutational cluster. Graphical Abstract: